The Russian Association for Engineering Education and its activity on specialists' Quality Perfection; World Congress on Engineering and Technology Education, WCETE 2004 (Guarujá/Santos, Brazil, March 14-17, 2004) - Pokholkov Y. P. Yuri Petrovich (2004, 2004)
The Russian Association for Engineering Education and its activity on specialists' quality perfection are presented in the report. The Russian Association for Engineering Education includes 60 regional departments established in the constituent territories of the Russian Federation. Here is brief review of the structure of the Russian Association for Engineering Education, its mission, major activities, goals and objectives, participation in different federal, regional and international programmes, cooperation with leading international organisations, situation in Russian engineering education, creation of independent structures of attestation and accreditation of educational programmes acknowledged abroad, certification of specialists and university lectures, assistance to improvement and development of engineering education